Work-life balance, motivation, and satisfaction as determinants of job commitment - Munda, Noel; Gache, Ma. Niña (International Journal of Educational Management and Development Studies, 2024)
This study evaluated the work-life balance, motivation, job satisfaction, and commitment levels of high school teachers in a city in Laguna, Philippines during the academic year 2022-2023. It narrowed the gap by testing if work-life balance, motivation, and job satisfaction predict job commitment level and if demographic profiles have moderation effect to the relationship between the predictors and outcome variable. Utilizing descriptive-correlational design, 262 teachers were surveyed through multi-stage sampling. Adapted questionnaires were utilized, content validated by experts, and verified through reliability testing. Mean, Standard Deviation, Spearman Rho, Ordinal Regression, and Moderated Regression were employed for data analysis. Results revealed that the teachers’ level of work-life balance, job satisfaction, and job commitment were high, while motivation was very high. Work-life balance had negative very weak correlation with job commitment, while job satisfaction had positive moderately strong correlation with job commitment. Motivation did not show any significant association with job commitment. Only job satisfaction had a significant effect on job commitment, whereas work-life balance and drive did not have significant effect. Age, years of teaching, and position had moderation effect, while sex had no moderation effect, on the link between work-life balance and job commitment, and between job satisfaction and teachers’ job commitment. Further, years of teaching years and position had moderation effect, while sex and age had no moderation effect, on the relationship between motivation and their job commitment. Results of the study had strong implications to the high school teachers, school heads and school administrators.